Cobalt ferrite films: nano-polishing and magnetic properties - Bilovol, Vitaliy (2014)
CoFe2O4 films were deposited on Si [(100) or (111)] substrates by pulsed laser deposition, varying substrate temperature and deposition time. All films showed highly (111)-preferred orientation. Magnetic measurements (hysteresis loops) at room temperature indicated that the films have in-plane magnetic anisotropy. By atomic force microscopy, the surface topology revealed an average roughness of approximately 15 nm due to the presence of droplets. To define the relevance of droplets on the films' magnetic properties, we applied a nanopolishing technique after which the surfaces became notoriously smoother. As a consequence of this surface modification, we found that the hysteresis loops (measured again after nanopolishing) revealed changes in the magnetic response of the samples. The thinner films ((t ~50) nm) revealed waist-type hysteresis loops with diminished values of the coercive field, while the thickest film ((t ~100) nm) increased its coercive field without qualitative change in its loop shape. We attributed the altered magnetic response to different mechanisms that depend on sample thickness. For the thinner films, an additional anisotropy (to that existing in the plane) was induced after the nanopolishing procedure. For the thickest film, it was observed that differences are present after the elimination of the droplets, showing their important role in the magnetic response of the films.